2016
DOI: 10.1016/j.bbmt.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Difficile Colonization in Hematopoietic Stem Cell Transplant Recipients: A Prospective Study of the Epidemiology and Outcomes Involving Toxigenic and Nontoxigenic Strains

Abstract: Clostridium difficile is a leading cause of infectious diarrhea in hematopoietic stem cell transplant (HSCT) recipients. Asymptomatic colonization of the gastrointestinal tract occurs before development of C. difficile infection (CDI). This prospective study examines the rates, risk factors, and outcomes of colonization with toxigenic and nontoxigenic strains of C. difficile in HSCT patients. This 18-month study was conducted in the HSCT unit at the Karmanos Cancer Center and Wayne State University in Detroit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
8
38
1
Order By: Relevance
“…A previous study found that prior colonization with toxigenic strains of Clostridium difficile strongly predicted for the development of CDI following allogeneic HPC transplant [6]. We found a history of CDI to be a strong predictive value for the development of PT-CDI.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A previous study found that prior colonization with toxigenic strains of Clostridium difficile strongly predicted for the development of CDI following allogeneic HPC transplant [6]. We found a history of CDI to be a strong predictive value for the development of PT-CDI.…”
Section: Discussionsupporting
confidence: 60%
“…A study found that gastrointestinal colonization with toxigenic Clostridium difficile occurred in 12% of recipients of HPC transplant on admission to the hospital [6]. In addition, these patients are immunocompromised, receive extensive exposure to broad spectrum antimicrobials before and after HPC transplant, have compromise of the integrity of the intestinal mucosa due to the high dose chemoradiation given to the patients as part of transplant preparative regimens, and also often have very prolonged hospital stay [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Jain T et al , 3 and Bruminhent et al , 4 reported a 12% and a 10.7% colonization rate at hospital admission, respectively, among their BMT population. Taken together, these studies suggest that the heme/BMT patient population is a significant reservoir of Clostridium difficile colonization, at least in large academic medical centers in the Midwest.…”
Section: Discussionmentioning
confidence: 95%
“…Toxigenic strains release exotoxins TcdA and TcdB to result in colitis and other diseases. Prevalence of C. difficile colonization for ICU patients [8], cancer patients [9, 10], patients undergoing hematopoietic stem cell transplantation [11, 12], residents in long-term care facilities [13], and healthy people [14] has been previously reported. The rates of C. difficile colonization in adult patients are different in different regions, but significantly lower than those in children [15].…”
Section: Introductionmentioning
confidence: 99%